Beyond Inclusion Worklife Interconnectedness, Energy, and Resilience in Organizations - Smith, J. Goosby. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Beyond Inclusion adopts a holistic and systems view of the organization, presents a behavioral model of organizational inclusion based upon research with thousands of employees, and discusses elements of organizational design that need to be adjusted to create, nurture, and sustain an inclusive culture.